Mini Electrostatic Precipitator System Model as a Smoke Particle Collector - Nugraha, Komang Ari Candra; Maulana, Eka; Djuriatno, Waru (Jurnal Mahasiswa TEUB, 2026)
Air pollution is one of the most pressing environmental issues today. The increase in industrial activities, transportation, and waste burning has significantly contributed to air pollution. This study aims to design and develop a Mini Electrostatic Precipitator (ESP) as a solution to capture smoke particles in the air. The research problems include the working principle of the device, its manufacturing process, and the resulting electric field strength and corona voltage. The study is limited to prototype development, measuring air quality from waste burning, and focusing on the manufacturing and operational aspects of the device. The ESP operates using the principle of high-voltage direct current and two types of electrodes to capture charged particles. The results indicate that the mini ESP can reduce smoke particles in the air, providing a practical solution to address air pollution in household environments and small industries. Keywords: Air Pollution, Electrostatic Precipitator, High Voltage, Smoke Particles